Pontoniinae (Crustacea: Decapoda: Caridea) from Brazil with taxonomic key - Vieira, Rony R.r.; Ferreira, Rodrigo S.; D’incao, Fernando (Zootaxa, 2012)
The subfamily Pontoniinae is represented by 116 genera in the world, of which Ancylomenes, Cuapetes, Holthuisaeus, Lipkebe, Neopontonides, Periclimenaeus, Periclimenes, Pontonia, Pseudocoutierea, Pseudopontonides, Typton, and Urocaris occur in Brazilian coast waters. This study presents distributional information, currents taxonomic and an identification key for species of Pontoniinae that occur in Brazilian coast.